Israel, church, and the gentiles in the Gospel of Matthew - Konradt, Matthias (Waco, Texas: Baylor University Press, 2014)
"Explores the relationship between the particular salvation of the Jews and the universal salvation of all people in the gospel of Matthew"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Theology; Bible. Matthew. -- Criticism, interpretation, etc; Bible. Matthew. -- Theology; RELIGION / Christianity / History